The Developmental Regulator pcz1 Affects the Production of Secondary Metabolites in the Filamentous Fungus Penicillium Roqueforti - Levican-Jaque, G; Chavez-Rosales, R; Gil-Duran, C; Rojas-Aedo, J (Elsevier GmbH, 2018)
Penicillium roqueforti is used in the production of several kinds of ripened blue-veined cheeses. In addition, this fungus produces interesting secondary metabolites such as roquefortine C, andrastin A and mycophenolic acid. To date, there is scarce information concerning the regulation of the production of these secondary metabolites. Recently, the gene named pcz1 (Penicillium C6 zinc domain protein 1) was described in P. roqueforti, which encodes for a Zn(II)2Cys6 protein that controls growth and developmental processes in this fungus. However, its effect on secondary metabolism is currently unknown. In this work, we have analyzed how the overexpression and down-regulation of pcz1 affect the production of roquefortine C, andrastin A and mycophenolic acid in P. roqueforti. The three metabolites were drastically reduced in the pcz1 down-regulated strains. However, when pcz1 was overexpressed, only mycophenolic acid was overproduced while, on the contrary, levels of roquefortine C and andrastin A were diminished. Importantly, these results match the expression pattern of key genes involved in the biosynthesis of these metabolites. Taken together, our results suggest that Pcz1 plays a key role in regulating secondary metabolism in the fungus Penicillium roqueforti. © 2018 Elsevier GmbH